Supramolecularly functionalized platelets for rapid control of hemorrhage. (1st September 2022) - Ding, Yuan-Fu; Huang, Qiaoxian; Quan, Xingping; Cheng, Qian; Li, Shengke; Zhao, Yonghua; Mok, Greta S.P.; Wang, Ruibing
Abstract: Excessive bleeding has always been of great medical challenge, particularly in trauma and surgery. Due to the fast clearance of medicine and complex hemodynamics during hemorrhage, it is often difficult to achieve rapid and effective hemostasis on irregularly shaped, noncompressible visceral bleeding wounds. Herein, we report a hemostatic derived from supramolecularly functionalized platelets (SPLTs), showing rapid hemorrhage controlling effects via efficiently targeting injured vessels and in-situ aggregation. Von Willebrand factor-binding peptide (VBP) modified hyaluronic acid (HA-VBP) decorated platelets (PLTs) were fabricated via supramolecular host-guest interactions between cucurbit[7]uril (CB[7], a host molecule) modified on HA-VBP (HA-CB[7]-VBP) and adamantane (ADA, a guest molecule) anchored on the surface of PLTs (ADA-PLTs). The SPLTs demonstrated approximately 10-fold improvements than the native PLTs in the targeting efficiency into the injured vessels in mice upon intravenous injection. More significantly, the total bleeding time and bleeding volume were dramatically reduced down to less than 1/4 and 1/10 of the control group, respectively, in both external and internal major bleeding mice models. This SPLTs provide a facile yet effective approach for rapid control of major hemorrhage and offers important new insights to the design and development PLTs-based hemostatics. Statement of significance: Hemorrhage is one of the greatest threats to humans in trauma and surgery. To reduce bleeding volume and time, transfusion of hematological products such as platelets (PLTs)-rich plasma is one of the most commonly used therapeutics, but with low targeting and hemostatic efficiency. Thus, engineered PLTs with expanded structural repertoire and functionalities are in urgent clinical needs. Herein, we developed supramolecularly functionalized PLTs (SPLTs), prepared with a mild and facile approach, for rapid control of hemorrhage with significantly enhanced targeting efficiency. The SPLTs not only provide a facile approach for rapid control of major hemorrhage, but also offer important new insights into the development PLTs-based hemostatics. Graphical abstract: Image, graphical abstract